Kepemimpinan Kepala Sekolah Dalam Fasilitasi Pengembangan Modul Backward Design yang Efektif: Studi Kasus di SD Skouw Jayapura - Yuliana S, Chelsi; Sukmawati, Sukmawati (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study investigates the principal's leadership role in overcoming challenges faced by teachers in developing Backward Design-based teaching modules in primary schools in the Skouw border area. Teachers encounter obstacles such as difficulties in formulating learning objectives, varying levels of technology proficiency, and physical environmental disruptions. Employing a qualitative method with semi-structured interviews, this research aimed to analyze how school principals facilitate teachers throughout the module development process. The results indicate the central role of the principal in providing facilitation through vision setting, offering training and resource support, fostering teacher collaboration, and conducting monitoring and evaluation. Although teachers were highly motivated, challenges related to conceptual understanding, technological limitations, and time management persisted. The implementation of the modules proved to have a positive impact on student enthusiasm and active participation. This research contributes to the literature on school leadership and teacher professional development within the context of a border region. It is concluded that supportive and adaptive principal leadership is the key to the success of instructional innovation in overcoming challenges and improving educational quality.